Comparison of two different doses of dexmedetomidine for continuous epidural analgesia for lower limb surgeries: A randomized double-blind study - Pranjali Kurhekar; Sam Blessy Sheba; Sathyasuba Meenakshisundaram; Raghuraman M. Sethuraman; Neeta Parlikar (Wolters Kluwer Medknow Publications, 2024)
Background and Aims: Bolus epidural dexmedetomidine provides potent analgesia but the incidence of hemodynamic instability is high. There are only a few studies that have evaluated the efficacy of epidural dexmedetomidine infusion but none of them compared different doses to find the optimum safe dose. We compared the analgesic efficacy and safety of two different doses of dexmedetomidine in continuous epidural for postoperative analgesia. Material and Methods: Patients undergoing lower limb surgeries were divided randomly into two groups: Group I (n = 36) received an epidural infusion of 0.1% ropivacaine + 0.5 μg/kg/24 h of dexmedetomidine and Group II (n = 36) received epidural infusion 0.1% ropivacaine + 1 μg/kg/24 h of dexmedetomidine. Both groups received epidural infusion at the rate of 5 ml/h over 48 h postoperatively. Pain scores, demand for rescue analgesics, hemodynamic parameters, and sedation scores were compared between the groups. Statistical analysis was done using an independent t-test and Chi-square test. Results: 1 μg/kg group (Group II) had a significantly reduced pain score at all time intervals and less demand for rescue analgesia (P = 0.03). The severity of pain was more in the 0.5 μg/kg group (Group I), at all times (P = 0.000). Incidence hypotension was higher in Group II. Bradycardia was seen in two patients in Group II and none in Group I. Conclusion: Dexmedetomidine in a dose of 1 μg/kg/24 h with 5 ml of 0.1% ropivacaine through epidural infusion provides better analgesia with a safe hemodynamic profile.